Assessing the EU's Added Value in the Area of Terrorism Prevention and Violent Radicalisation - Raphael Bossong (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper questions the effectiveness and the prospects of EU efforts to prevent terrorism and violent radicalisation. After the terrorist of attacks of Madrid and London,, member states agreed on a comprehensive strategy to prevent radicalisation and recruitment into terrorism, but simultaneously underlined the limits of EU competences. The European Commission therefore focused on indirect measures, such as research support. Over time, however, both flexible cooperation among a subset of member states and new EU initiatives generated few or biased policy outputs. The second part of the paper questions the resulting proposal to create a network of local or sub-national actors for best practice exchange. It is argued that preventive counterterrorism relies on contentious scientific evidence and that authoritative evaluations remain tied to national policy-making. Finally, the EU Commission cannot mobilise sufficient resources to ensure that 'frontline' organisations, such as police services, implement new practices. The conclusions raise further research questions on the use of knowledge and complex governance patterns in EU internal security.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330